Assessment of Strategy Disclosure Drivers in Annual Company Report: A Meta-Synthesis Analysis - Akram Taftiyan; Mohammad Salari Abarghuoi (تحقیقات مالی)
Objective Disclosure of strategy in annual reports by companies is a method of transmitting information related to the performance of the company's strategy and its effects on stakeholders, and identifying the drivers and factors affecting it is considered important due to the important role of this type of reporting in making correct and informed decisions. The purpose of this study is to investigate the drivers of strategy disclosure in the companies’ annual reports. Revealing a company's corporate strategy to the public is seen as reliable because managers prioritize safeguarding their reputation. This commitment to transparency encourages a company's leadership to make meaningful investments in the strategy. While disclosing forward-looking statements, like the progress of business strategies' implementation, in annual reports offers insight into the company's direction from management to financial analysts, it can also entail certain costs by potentially harming the company's competitive position.